Association between Inflammatory and Metabolic Biomarkers and Common Mental Disorders among Adults: 2015 Health Survey of São Paulo, SP, Brazil - Letícia do Nascimento Maximiano Ferreira; Regina Mara Fisberg; Flavia Mori Sarti; Marcelo Macedo Rogero (Metabolites)
Recent studies suggest that plasma inflammatory biomarker concentrations may represent valuable indicators for the diagnosis and prognosis of mental disorders. At the same time, metabolic alterations may contribute to the development and progression of systemic low-grade inflammation. Background/Objectives: This study evaluated the association between plasma inflammatory biomarkers and common mental disorders (CMD), exploring the relationship between metabolic biomarkers, metabolic syndrome (MetS), and inflammatory biomarkers in younger and older adults. Methods: This cross-sectional study used data from the 2015 Health Survey of São Paulo with a Focus on Nutrition Study. The occurrence of CMD was assessed through the Self-Reporting Questionnaire (SRQ-20). Blood samples were used to measure plasma concentrations of inflammatory and cardiometabolic biomarkers. MetS was defined according to the International Diabetes Federation Consensus. The Mann–Whitney test compared inflammatory biomarker concentrations across CMD groups and cardiometabolic conditions, and logistic regression models explored associations between inflammatory biomarker concentration and CMD. Results: The sample included 575 participants, 22.6% (n = 130) of whom had CMD. Concentrations of plasminogen activator inhibitor 1, C-reactive protein (CRP), and the systemic low-grade inflammation score varied significantly among CMD groups. CRP concentrations were positively associated with the presence of CMD, independent of confounding factors. Participants with insulin resistance, dyslipidemia, and MetS exhibited significantly higher CRP concentrations than individuals without these conditions. Conclusions: The findings suggest that increased plasma CRP concentrations may be a potential risk factor for CMD. Higher CRP concentrations were observed in individuals with insulin resistance, dyslipidemia, and MetS. Future interventional studies should explore these hypotheses in diverse populations.